The rural panopticon. (April 2017) - Philo, Chris; Parr, Hester; Burns, Nicola
Abstract: As a contribution to both rural theory and a geography of rural disability, this paper tackles the idea of the 'rural panopticon'. Inspired by empirical research on mental ill-health in the Scottish Highlands, the authors specify certain workings of the rural panopticon, stressing interconnections between visibility, observation, surveillance, chatter and interiorised senses of self-disciplining (particularly for those with fragile mental health). There are suggestions that Bentham regarded his institutional brain-child, the Panopticon, as most logically and properly an urban phenomena, even calling it 'Panopticon Town', but there is a supplementary argument that identifies a rural vision – of a virtuous, self-regulating farming community – present in the margins of his Panopticon thinking. Through the figure of the 'glass palace' in the countryside, emphasising the pervasive watching, judging and censuring of conduct, a further link is made from Bentham's Panopticon to the rural panopticon. The paper explores this link both textually and though the Highlands case study, concluding by examining Foucault's dual attention to both Bentham's Panopticon and a rural colony for delinquent boys, Mettray, as twin exemplars of 'panopticism' in the disciplining of troublesome and troubled populations (those with disabilities included). Highlights: New theoretical development – specifying 'the rural panopticon'. Tracing rural dimensions of Bentham's original 'Panopticon' vision – never done at all systematically before. Applying the theoretical framework to a Highlands case study. Signposting new directions for work on rurality, rural geography and the geography of rural disability.